Public-goods games with endogenous institution-formation: Experimental evidence on the effect of the voting rule - Yukihiko Funaki; Jiawen Li; Róbert F. Veszteg (Games, 2017)
We report experimental results on voluntary contributions to public-goods provision from situations in which parties can create institutions to impose a certain contribution level on its members. We focus on a public-goods game where the joint decisions inside the institution are made based on the plurality voting rule. We show that, comparing to the unanimity voting rule, the plurality rule results in a significant and large decrease in the institution initiation rate, along with a significant and large increase in the institution implementation rate. In the end, as the two effects cancel each other out, the choice of the voting rule does not significantly affect the average contribution level or efficiency.
Keywords: C91; C92; H41; 330; institution formation; laboratory experiment; plurality voting; public-goods game; unanimity voting